Knowledge of intellectual property laws as a moderator of the relationship between moral development and attitudes towards unauthorised copying of software - King, Bernadette (My University, 2008)
Different researchers commit themselves to differing hypotheses when addressing the relationship between attitudes to unauthorised copying of software and the level of moral development. Some concentrate on moral intensity, others on moral judgement and still others on ethical decision-making. Some researchers assert that no one single hypothesis is correct but that certain hypotheses will be true under certain conditions. The idea that there is no single correct hypothesis has paved the way for the consideration of moderator variables of the attitudes to unauthorised copying of software and the level of moral development relationship. One variable in particular, that is, the Knowledge of Intellectual Property laws, has not yet been empirically examined in terms of its capacity as a moderator for this relationship. This exploratory, non-experimental, cross-sectional design explores the relationship between attitudes to unauthorised copying of software and the level of moral development as well as the effect of Knowledge of Intellectual Property laws on this relationship. A questionnaire was distributed to three medium-sized organisations in the Johannesburg area. The questionnaire consisted of a biographical blank and three different scales. The biographical blank was used as a means of examining the computer background of the respondents whilst the scales measured respondent attitudes to unauthorised copying of software, levels of moral development and respondent knowledge of Intellectual Property laws. The researcher received responses from 150 respondents from across the three organisations. It was with these 150 responses that two types of analyses were conducted. The initial analysis was a Pearson’s Product-Moment Correlation which was used to determine the nature of the relationship between attitudes to unauthorised copying of software and level of moral development. The second analysis was a moderated multiple regression which was used to determine the moderator impact of Knowledge of Intellectual Property laws on the relationship between the independent and dependent variables. The results of the correlation indicated that there is a significant positive relationship between the respondents’ attitudes to unauthorised copying of software and the level of moral development. Additionally, there are significant relationships between each measured level of moral development with the respondents’ attitudes. The moderated multiple linear regression revealed that Knowledge of Intellectual Property laws does not have a moderating effect on the relationship between attitudes to unauthorised copying of software. A discussion of these findings is included together with limitations and practical implications of the study as well as recommendations for future research.
Keywords: moral development; unauthorised copying of software; intellectual property